ANALISIS SOSIOLOGI HUKUM ISLAM TERHADAP PELAKSANAAN ISBAT NIKAH OLEH PENGADILAN AGAMA - Mohammad Ali Fikri (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2016)
In Indonesia every moslem marriage should be recorded in KUA. But many people who still carry out the marriage without registration at KUA. It is in by several factors that happened in society. And then, when they want to record their marriage then they apply for a itsbat of marriage in Religious Courts. The implementation of itsbat marriages are funded by the community at Pasean Pamekasan. They are still upholding the Customs who has become the legacy of the ancestors. The research approach is used by the Writer in the preparation of this thesis are The approach in this study uses the approach of Fiqh, Usul Fiqh and Sociology with qualitative methods of research case study. The research data was collected via observation and interviews.Keyword : Itsbat nikah, KUA, Registrating of Mariage